Physical Activity with Play and Game Model to Improve The Cognitive of Elementary School Students - Humaid Ali Hasan; Sapto Adi; Eko Hariyanto; Arus Kongrungchok; Herlina Ike Oktaviani; Otto Fajarianto (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2023)
Elementary school age is a period of physical growth and movement that plays an important role in the formation of quality individuals. Through physical movements in the form of games that continue to provide optimal development in children both cognitive maturity and motor development. Sports with a play-and-game system can increase the growth of neurons in the brain and stimulate the growth of new neurons in the hippocampus. Meanwhile, physical education learning in elementary schools is still teacher-centered and there is still a lack of variety of learning models. Based on the above problems, the play-and-game model can be used as a monotonous and less interesting learning solution. This learning is effective and innovative because it can provide learning experiences both from cognitive, motor, and affective aspects. Engaging in physical activity will positively affect all systems: cardiovascular, respiratory, hormonal, immunological, and nervous systems. In addition, a large development of the frontal and temporal lobes at the age of children 7-12 years. The brain will become more rapidly developed so that it will make faster cognitive improvement. The Play and game model can improve academic performance both in memory, memory, and learning.